2020
DOI: 10.1210/clinem/dgaa543
|View full text |Cite
|
Sign up to set email alerts
|

Management and Appropriate Use of Diazoxide in Infants and Children with Hyperinsulinism

Abstract: Background The diagnosis of hypoglycemia and the use of diazoxide have risen in the last decade. Diazoxide is the only FDA-approved pharmacologic treatment for neonatal hypoglycemia caused by hyperinsulinism (HI). Recent publications have highlighted that diazoxide has serious adverse effects (AEs) such as pulmonary hypertension (2-3%) and neutropenia (15%). Despite its increasing use, there is little information regarding dosing of diazoxide and/or monitoring for AEs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 40 publications
1
50
1
Order By: Relevance
“…Diazoxide, the first line treatment of congenital HH, binds to the linker region of the SUR1 subunit of the KATP channels and suppresses β-cell insulin secretion by forcing the channels to remain open [20]. Early diazoxide administration was a solid judgment for our patient during HH events, even prior to genetic diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…Diazoxide, the first line treatment of congenital HH, binds to the linker region of the SUR1 subunit of the KATP channels and suppresses β-cell insulin secretion by forcing the channels to remain open [20]. Early diazoxide administration was a solid judgment for our patient during HH events, even prior to genetic diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…Another study demonstrated a much lower risk for severe adverse events (SAE) including PH associated with diazoxide use in those with genetic HH (3.6% with any SAE, 1.2% with PH) as compared to those with perinatal stress hyperinsulinism (16.7% with any SAE, 7.6% with PH) [ 17 ]. Currently, there is limited evidence on diazoxide dosing strategies, but the expert consensus of the members of the Drug and Therapeutics Committee of the Pediatric Endocrine Society emphasized the importance of reducing diazoxide dose if hyperglycemia occurs [ 18 ]. It thus remains unclear in our patient to what extent the low dose of diazoxide may have contributed to her decompensation, which was very likely primarily related to her underlying cardiopulmonary pathology.…”
Section: Discussionmentioning
confidence: 99%
“… 28 A normal hepatic and renal function tests and cardiac evaluation before diazoxide initiation are prerequisites to avoid complications. 29 …”
Section: Discussionmentioning
confidence: 99%
“…28 A normal hepatic and renal function tests and cardiac evaluation before diazoxide initiation are prerequisites to avoid complications. 29 Regular follow-up appointments continue with neonatologist, endocrinologist, neurologist, and neurosurgeon. Diazoxide was allowed to self-wean with weight gain.…”
Section: Discussionmentioning
confidence: 99%